Klasifikasi Emosi Tokoh Utama dalam Novel Moga Bunda Disayang Allah Karya Tere Liye: Perspektif David Krech - Anisa Yusni Putri; Nesa Riska Pangesti (Asian Journal of Islamic Studies and Da'wah, 2026)
The novel Moga Bunda Disayang Allah by Tere Liye portrays the inner struggle of a human being facing life’s conflicts through the main character, Karang, who experiences traumatic events and intense emotions. This study aimed to classify the emotions of the main character as reflected in Karang’s characterization in the novel, based on David Krech’s literary psychology perspective. A descriptive–analytical method was employed, grounded in David Krech’s emotional classification within literary psychology. The research data consisted of words, phrases, clauses, and sentences containing emotional aspects of Karang, drawn from the fifth edition (February 2024) of Moga Bunda Disayang Allah. Data were collected through intensive reading and note-taking, while data validity was ensured using triangulation techniques. The findings show that Karang experiences seven primary types of emotions: guilt, repressed guilt, self-punishment, shame, sadness, hatred, and love. Guilt emerges as the most dominant emotion, shaping his initial characterization as stubborn, egocentric, and indifferent. Through Karang’s interactions with Melati and the family of Tuan HK, the emotion of love develops and drives his personality transformation into a more caring, affectionate, and considerate figure. Thus, the dynamics of Karang’s emotions represent an inner transformation process from suffering toward acceptance and emotional recovery, while simultaneously affirming the humanistic message conveyed by the author and enriching literary psychology studies on the representation of emotion in fiction.